2009
DOI: 10.1038/cr.2009.143
|View full text |Cite
|
Sign up to set email alerts
|

The AGL6-like gene OsMADS6 regulates floral organ and meristem identities in rice

Abstract: Although AGAMOUS-LIKE6 (AGL6) MADS-box genes are ancient with wide distributions in gymnosperms and angiosperms, their functions remain poorly understood. Here, we show the biological role of the AGL6-like gene, OsMADS6, in specifying floral organ and meristem identities in rice (Oryza sativa L.). OsMADS6 was strongly expressed in the floral meristem at early stages. Subsequently, OsMADS6 transcripts were mainly detectable in paleas, lodicules, carpels and the integument of ovule, as well as in the receptacle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 60 publications
8
147
0
3
Order By: Relevance
“…OsMADS34/PANICLE PHYTO-MER2 (PAP2) regulates the development of inflorescences and spikelets 39,40 . Emerging evidence suggests that ancient AGAMOUS-LIKE6 (AGL6)-like genes conserved in gymnosperns and angiosperms, such as rice OsMADS6/MOSAIC FLORAL ORGANS1 (MFO1) [53][54][55] and maize zea agamous3 (zag3) 56 , the close homologues of SEP-like genes, have SEP-like functions essential for flower development. In this study, we show a previously unreported JA pathway that regulates the expression of OsMADS1, OsMADS7 and OsMADS8 in rice spikelet development, linking the upstream JA pathway to the floral meristem identity genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…OsMADS34/PANICLE PHYTO-MER2 (PAP2) regulates the development of inflorescences and spikelets 39,40 . Emerging evidence suggests that ancient AGAMOUS-LIKE6 (AGL6)-like genes conserved in gymnosperns and angiosperms, such as rice OsMADS6/MOSAIC FLORAL ORGANS1 (MFO1) [53][54][55] and maize zea agamous3 (zag3) 56 , the close homologues of SEP-like genes, have SEP-like functions essential for flower development. In this study, we show a previously unreported JA pathway that regulates the expression of OsMADS1, OsMADS7 and OsMADS8 in rice spikelet development, linking the upstream JA pathway to the floral meristem identity genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and physical interactions of OsMADS1 suggest that in promoting FM identity, it acts in conjunction with a SEP sister clade (AGL6-like) member, MOSAIC FLORAL ORGANS1/OsMADS6 (Ohmori et al, 2009;Li et al, 2010), and with OsMADS15/DEP, an APETALA1/FRUITFULL-like homolog (Supplemental Fig. S8).…”
Section: Osmads1 Promotes Fm Identity and Its Maintenancementioning
confidence: 99%
“…OsMADS1, OsMADS6, other SEP genes, and class C and D genes (OsMADS3, OsMADS58, OsMADS13, OsMADS21, OsMADS7, and OsMADS8) contribute to rice FM termination (Yamaguchi et al, 2006;Ohmori et al, 2009;Li et al, 2010Li et al, , 2011aSupplemental Fig. S8).…”
Section: Interactions Among Mads Factors During Floret Organogenesis mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four AG subfamily genes of rice, MADS3, MADS13, and MADS58 regulate also FM determinacy, whereas MADS21 seems not to play important functions during flower development. The MADS domain proteins shown in this model might interact with SEP-like and/or AGL6-like MADS domain proteins providing E-function (Favaro et al, 2002;Kater et al, 2006;Ohmori et al, 2009;Cui et al, 2010;Li et al, 2010;Li et al, 2011a), which for simplicity are not shown in this scheme.…”
Section: The Role Of Ag Subfamily Genes In Ovule Developmentmentioning
confidence: 99%